2019
DOI: 10.1088/1755-1315/301/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted solvent extraction oil from dried rice bran soapstock

Abstract: In this study, neutral oil was recovered from dried rice bran soapstock using ultrasound assisted solvent extraction (UASE). Response surface methodology (RSM) was employed to optimize the UASE parameters to obtain the maximum yield of neutral oil using face centered composite design (FCCD). The parameters included ultrasound power (0.5-4.5W/g), process temperature (35-55°C), and sonication time (4-26 min). The quadratic response models were generated and statistical analysis was performed to validate the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The adequacy and reliability of the regression model were presented in Table 3. This study found that the respective values of R 2 and adj-R 2 , and predict R 2 for the recovery of triterpenoids (0.98, 0.95, and 0.83, respectively) and ABTS (0.95, 0.88, and 0.70, respectively) were close 1, which indicated good agreement between the experimental and predicted results [19,20]. The high p-values of lack of fit tests proved that the models are generated well.…”
Section: Model Fittingsupporting
confidence: 52%
See 1 more Smart Citation
“…The adequacy and reliability of the regression model were presented in Table 3. This study found that the respective values of R 2 and adj-R 2 , and predict R 2 for the recovery of triterpenoids (0.98, 0.95, and 0.83, respectively) and ABTS (0.95, 0.88, and 0.70, respectively) were close 1, which indicated good agreement between the experimental and predicted results [19,20]. The high p-values of lack of fit tests proved that the models are generated well.…”
Section: Model Fittingsupporting
confidence: 52%
“…However, the contents of triterpenoids and antioxidant activity values slightly decrease as ultrasonic power and temperature processes increased from 250 to 350W and 45 to 60°C, respectively. Phan et al ( 2020) reported that the cell membrane may break into small fragments under high temperature and ultrasonic power processes, which leads to increase impurities being extracted, thus a decrease in the recovery of bioactive compounds extracted [19]. Tran et al (2021) reported that high temperature (over 60°C) destroyed the triterpenoid molecular structure of the five rings, resulting in a low level of triterpenoids and making these compounds less effective [15].…”
Section: Effects Of Extraction Conditions On the Recovery Of Triterpe...mentioning
confidence: 99%
“…The result of research from Ref. [ 26 ] show that The second order kinetic parameters of the gamma oryzanol extraction model from dried rice bran soapstock show that the values of Cs, k and h increase with increasing ultrasonic power (from 0.5 W/g to 4.5 W/g) and extraction temperature (from 35 °C to 45 °C). Cs and h decreased when the extraction temperature increased from 45 °C to 55 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Studying different types of solvents to evaluate the extraction and subsequent recovery of the compounds of interest is very important, since the chemical characteristics of each solvent act on the matrix, recovering more or less compounds according to their characteristics, such as ionic strength, matrix composition, hydrogen‐bond interactions or channel effect. It was supported by using supercritical fluid extraction (Jesus et al ., 2010; Kayathi et al ., 2021), deep eutectic solvente (Niawanti & Zullaikah, 2017; Zullaikah et al ., 2019) or with conventional solventes (Wangdee & Onsaard, 2018; Daisuk & Shotipruk, 2020; Phan et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studying different types of solvents to evaluate the extraction and subsequent recovery of the compounds of interest is very important, since the chemical characteristics of each solvent act on the matrix, recovering more or less compounds according to their characteristics, such as ionic strength, matrix composition, hydrogen-bond interactions or channel effect. It was supported by using supercritical fluid extraction (Jesus et al, 2010;Kayathi et al, 2021), deep eutectic solvente (Niawanti & Zullaikah, 2017;Zullaikah et al, 2019) or with conventional solventes (Wangdee & Onsaard, 2018;Daisuk & Shotipruk, 2020;Phan et al, 2020). Daisuk & Shotipruk (2020) developed an effective procedure for the recovery of γ-oryzanol through calciuminduced precipitation (Ca) of the raw material of RBO (RBOS), a by-product of the RBO industry, where one of the studied variables was the type of solvent used in extraction (chloroform, DCM, acetone, ethyl acetate, furfural, isopropanol, hexane, ethanol and methanol).…”
Section: Single-step Extraction Process (Simple Extraction)mentioning
confidence: 99%